Influence of the pin diameter to spacing ratio in metal/composite joints joined via metallic pin structures - Julian Popp; Jan Gavelek; David Römisch; Marion Merklein; Dietmar Drummer (Journal of Advanced Joining Processes)
Joining metal components with thermoplastic composites via the embedding of pin structures is a promising novel mechanical joining technology to create lightweight hybrid components. In the current state of the art, it is not understood which influence the pin size and pin arrangement in a multi pin array has on the mechanical performance of the created joints. In the scope of the present study different pin arrays have been used to create joints between stainless steel and unidirectionally reinforced thermoplastic composites. Thereby the pin density, which describes the fraction of the joint surface is occupied by pin structures, in the joint is kept constant and the pin size and pin arrangement has been varied. It shows that a higher number of smaller pins leads to better mechanical performance under both shear as well as normal testing load. Furthermore, an asymmetric pin arrangement, where one out of two pin rows is offset perpendicular to the fiber orientation, increased joint strength. The achieved shear strength of the samples reaches up to 10.8 MPa while the achieved normal strength is significantly lower at a maximum of 2.3 MPa.